2019
DOI: 10.1038/s41405-019-0026-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of a hydroxyapatite and a fluoride toothpaste for prevention and remineralization of dental caries in children

Abstract: ObjectiveThis in situ study compared the effectiveness of two toothpastes containing hydroxyapatite or 500 ppm fluoride in promoting remineralization and inhibiting caries development.Materials and methodsTwo enamel blocks (human primary teeth), one sound and one with artificially-produced caries lesion, were exposed to toothpaste containing either 10% hydroxyapatite or 500 ppm F− (amine fluoride) via intra-oral appliance worn by 30 adults in two-arm double blind randomized crossover study lasting 14 days per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
117
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(140 citation statements)
references
References 50 publications
8
117
0
Order By: Relevance
“…They explained the discrepancy to the findings from Huang et al by different components in their remineralization/demineralization buffers (mainly proteins) which may block the enamel surface to some extent [36]. In a recent in situ-study, Amaechi et al found remineralization of artificially produced carious lesions on enamel blocks that were worn in situ on intra-oral appliances after use of a toothpaste containing 10% HAP [39].…”
Section: Discussionmentioning
confidence: 91%
“…They explained the discrepancy to the findings from Huang et al by different components in their remineralization/demineralization buffers (mainly proteins) which may block the enamel surface to some extent [36]. In a recent in situ-study, Amaechi et al found remineralization of artificially produced carious lesions on enamel blocks that were worn in situ on intra-oral appliances after use of a toothpaste containing 10% HAP [39].…”
Section: Discussionmentioning
confidence: 91%
“…33 In contrast, other in vitro and in situ studies have shown a remineralizing effect of HAP-containing toothpastes on enamel and/or dentin surfaces. Recent studies were published by Tschoppe et al 27 (in vitro study), Najibfard et al, 26 and Amaechi et al 28 (the latter are in situ studies).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a positive influence on the remineralization/demineralization process is very likely. 20,[26][27][28]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the recently proposed whitening agents is hydroxyapatite (HAP), which is the main component of dental hard tissues and bone and can be artificially synthesized [5]. HAP is used in dental treatments, such as for preventing enamel caries, restoring initial cavities, nano-hydroxyapatite-containing glass ionomer cements, and removing dental plaque in addition to hydroxyapatite-containing tooth pastes [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%